HPV infection detected by hybrid capture II: correlation with morphological findings - Dôres, Gerson B. (2005)
Introduction: HPV is a necessary but not sufficient cause for cervical cancer. Its crucial identifies HPV infection to establish the risk of cervicallesion. The Hybrid Capture (HCII) is recognized as method of choice to be used in routine conditions. Morphological methods (colposcopy, cytologyand histopathology), are very specific to demonstrate HPV-induced lesions. Objective: to compare the performance of morphological methods tosuggest HPV with HC II. Methods: 2871 consecutive samples, previously HPV infection suggested by colposcopy and/or cytology and/or histopa-thology, were submitted for HCII assay with high risk HPV probes (16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, 68). Sensitivity, specificity, accuracy and negative (NPV) and positive (PPV) predictive values were calculated taking in account the HCII results as gold standard. Results: we didnot identified HPV infection with HCII in 1.761 cases with colposcopic diagnosis suggestive of HPV infection, The colposcopy specificity was 14.5%, the sensitivity 88.9%, the accuracy 35.5% and the Negative (NPV) and Positive (PPV) predictive values were 76.9% and 29.1%, respectively. Cytology correctly suggested HPV in 503 cases with specificity of 56%, sensitivity of 62.0%, accuracy of 57.7% and NPV and PPV of 78.9% e35.7%, respectively. Histopathological diagnosis showed 709 cases suggestive of HPV-induced lesion confirmed by HCII, resulting in specificity of15.1%, sensitivity of 87.4%, accuracy of 35.6% and NPV and PPV of 75.4% and 28.9%, respectively. Together, morphological methods showed asensitivity of 94.1%, specificity of 10.3%, and accuracy of 34.0%. Conclusion:among the morphological methods, despite its poor performance, cytology showed the best parameters to identify HPV infection. The sensitivity, but not the specificity, was improved with the morphological methods association. By that reason, biomolecular methods are required to confirm suspected morphological HPV infection